2016
DOI: 10.1093/ndt/gfw039
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing pathological ankle-brachial index values along the chronic kidney disease spectrum: the NEFRONA study

Abstract: Asymptomatic PAD is very prevalent in all CKD stages, but factors related to a low or high pathological ABI differ, revealing different pathogenic pathways. Diabetes, dyslipidaemia, inflammation and mineral-bone disorders play a role in the appearance of PAD in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 49 publications
3
31
1
1
Order By: Relevance
“…Studies had shown that OPG levels could be modulated by inflammatory cytokines, and the presence and severity of PAD were correlated with inflammation [10,11,17,20]. In a multicenter prospective study, high-sensitivity CRP was significantly associated with abnormal ABI levels, revealing that inflammation played a role in the PAD pathogenesis [17]. Moreover, in patients on PD who had PAD, lower albumin and higher CRP levels were found respectively than those without PAD [20].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies had shown that OPG levels could be modulated by inflammatory cytokines, and the presence and severity of PAD were correlated with inflammation [10,11,17,20]. In a multicenter prospective study, high-sensitivity CRP was significantly associated with abnormal ABI levels, revealing that inflammation played a role in the PAD pathogenesis [17]. Moreover, in patients on PD who had PAD, lower albumin and higher CRP levels were found respectively than those without PAD [20].…”
Section: Discussionmentioning
confidence: 97%
“…In the National Health and Nutrition Examination Survey, participants with estimated creatine clearance of <60 mL/min/1.72 m 2 had a 2.5-fold higher risk for developing PAD than those with >60 mL/min/1.72 m 2 , independent of traditional factors [16]. With the advancement of CKD, the PAD prevalence also increased as compared with the normal renal function [17]. Moreover, a nationwide cohort study conducted in Taiwan showed that the overall PAD incidences were 24.2, 12.4, and 20.7 per 1,000 person-years with respectively 4.4-fold, 2.78-fold, and 3.94-fold increased risks in the HD, PD, and all ESRD patients, which emphasized renal function as a risk factor for PAD [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified method was chosen for a higher sensitivity, selecting in each patient the most pathological of the four values. [ 24 ] A pathologic ABI was defined as a value ≤0.9 (diagnostic of limb ischemia) or ≥1.4 (related to arterial incompressibility and stiffness, usually ascribed to vascular ageing degeneration).…”
Section: Methodsmentioning
confidence: 99%
“…Current health status, medical history, baseline cardiovascular risk factors, and drug use information was obtained at baseline. A physical examination was performed, consisting of anthropometric measures, standard vital tests, and ABI measurements as previously described (24). A pathologic ABI was described as #0.9 or $1.4.…”
Section: Clinical Data and Laboratory Examinationsmentioning
confidence: 99%